P2-41. Relationship between genetic influence in low gamma band ERD and linguistic ability. Issue 9 (September 2017) - Araki, Toshihiko; Hirata, Masayuki; Yanagisawa, Takufumi; Sugata, Hisato; Onishi, Mai; Honda, Chika; Iwatani, Yoshinori; Yorifuji, Shiro
Abstract : Twin studies have suggested that there are genetic influences on inter-individual variation in regard to linguistic abilities. However, the brain activities under genetic influence during linguistic processing remain unclear. In this study, we investigated neuromagnetic activities during a verb generation task in a group of 28 monozygotic (MZ) and 12 dizygotic (DZ) adult Japanese twins. We examined the spatio-temporal distribution of the event-related desynchronizations (ERDs) in the low gamma band (25–50 Hz) using beamformer and time–frequency analyses. Heritability was evaluated by comparing the respective MZ and DZ intra-class correlations. The genetic and environmental contributions were estimated by structural equation modeling (SEM). We found that the peaks of the low gamma ERDs were localized to the left frontal area. The power of low gamma ERDs in this area exhibited higher similarity between MZ twins than that between DZ twins. SEM estimated the genetic contribution as approximately 50%. In addition, these powers were negatively correlated with the behavioral verbal scores. These results shows that low gamma ERDs in the left frontal area during a language task are influenced equally by genetic and environmental factors, and the subjects with higher verbal scores had lower powers for these ERDs.